Behavior of market prices and analysis of volatility for peach (Prunus persica [L.] Batsch.) produced in Boyaca, Colombia (2017)
At present, there are different studies on deciduous fruits, including the peach, for subjects such as production, harvest, postharvest, and markets. However, for developing the formulation of investment projects, the behavior of fruit prices in the most representative markets of the country are unknown for recent years. This research focused on the analysis of peach prices in three markets in Colombia: (a) Central de Abastos of Bogota, (b) Wholesaler of Antioquia, Medellín and (c) Reten Sur de Tunja, with the objective of verifying whether seasonality and volatility in market prices have occurred during the period 2006 to 2011, even more so when small producers report that agribusiness is becoming less profitable. When new projects are developed to invest in these species, difficulty in the allocation of sales prices is seen. This increases risk in decision making for producers. The study began with the analysis of the generalities of production of deciduous fruits and peaches, a product that is concentrated mainly in the department of Boyacá, Colombia, in agribusinesses of smallholders with a rural economy. It continued with the relation of data of prices per kg/month between the years 2006 and 2011. In the three markets, the methodology used an exploratory analysis of the prices by means of the Singular Spectral Analysis, along with the Loess Method and the Box and Jenkins methodology. It was possible to determine the trend behavior and seasonality in the peach prices. On the other hand, it was observed that a seasonal and trend behavior was not present in the markets of Corabastos of Bogota or Central Wholesale of Antioquia, but seasonality was seen in the market of Tunja. It should be emphasized that the price volatility was not observed in the three markets; it was determined that the current average price per kg of peach fruits in the Reten Sur de Tunja market is $1,800 Colombian Pesos (USD 0.60) and $3,500 Colombian Pesos (USD 1.17) in the Bogotá and Medellin markets, respectively.